Surface rust-proof treatment method for stator punching sheet
By constructing a multi-dimensional protective layer on the surface of the stator laminations, the shortcomings of traditional rust prevention treatments under complex working conditions and environmental problems have been solved, achieving a highly efficient and environmentally friendly rust prevention effect and extending the service life of new energy vehicles and industrial servo motors.
Patent Information
- Application Number
- CN202511026268.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-24
- Publication Date
- 2025-12-12
AI Technical Summary
Traditional stator lamination rust prevention processes are insufficient in providing protection under complex conditions such as high temperature, high humidity, and salt spray. They also involve the use of heavy metals and the emission of organic solvents, making it difficult to meet the high-precision equipment requirements of new energy vehicles and industrial servo motors.
Low-pressure plasma pretreatment is used to form a nanoscale rough structure, combined with biomimetic mineralization reaction to generate a hydroxyapatite biomimetic film, and then a nanoscale anti-rust film is formed through supramolecular self-assembly. The gradient composite coating includes a water-based inorganic zinc-rich primer, a carbon nanotube forest intermediate layer and an MXene nanosheet paint. Finally, photoresponsive pore sealing treatment is performed to form a multi-dimensional protective layer.
It significantly improves the rust resistance of stator laminations, with a rust resistance duration of over 2000 hours in salt spray tests, and a service life extended by 2.5 times under high temperature and high humidity conditions. It also reduces the use of heavy metals and organic solvents, meeting environmental protection requirements.
Smart Images

Figure CN121103655A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of metal material protection, in particular to a stator lamination surface rust-proof treatment method. BACKGROUND
[0002] As a core component of the motor, the surface rust-proof performance of the stator lamination directly affects the service life and operation reliability of the motor. Traditional rust-proof treatment mostly adopts galvanizing, coating anti-rust paint and other processes. Although the galvanizing process can form a dense metal protective layer, high-temperature treatment can easily cause the lamination to deform, and the zinc layer is prone to galvanic corrosion in a humid and hot, acidic and alkaline environment. The anti-rust paint coating has the problems of insufficient adhesion between the coating and the substrate and poor weather resistance, and the coating is prone to cracking and peeling after long-term use, losing its protective effect. With the development of new energy vehicles, industrial servo motors and other high-precision equipment, higher requirements are put forward for the rust-proof performance, dimensional accuracy and environmental friendliness of the stator lamination, and the traditional process has been difficult to meet the demand.
[0003] In recent years, new surface treatment technologies such as nano conversion film and silane coupling agent have been gradually applied to metal rust prevention. The nano conversion film forms a nano-scale protective layer on the metal surface through chemical film formation, but the density and self-repairing ability of the existing film layer are limited, and it cannot effectively resist the penetration of corrosion media such as chloride ions; although the silane coupling agent can enhance the adhesion between the coating and the substrate, the single film layer has weak rust-proof function and needs to be used in combination with other coatings, and the interface compatibility between the layers in the composite process is outstanding, resulting in unstable overall protection performance. In addition, these technologies focus on a single rust-proof mechanism and lack multi-scale and multi-dimensional collaborative protection design.
[0004] Under the trend of intelligent manufacturing and green manufacturing, the surface treatment of the stator lamination needs to break through the bottleneck of traditional technology. On the one hand, the long-term rust-proof problem under complex working conditions needs to be solved, such as the accelerated destruction of the protective layer by high temperature and humidity, salt spray and electromagnetic environment; on the other hand, the green and intelligent process needs to be considered, reducing the use of heavy metals and the emission of organic solvents, while achieving precise control of the surface treatment process. The application of existing technologies in the fields of biomimetic structure design, supramolecular self-assembly and light-responsive intelligent protection is still in the exploratory stage, and it is difficult to meet the demand for high performance and long service life of the stator lamination of high-end equipment. SUMMARY
[0005] (I) Technical problems solved In view of the deficiencies of the prior art, the present application provides a stator lamination surface rust-proof treatment method.
[0006] (II) Technical solutions A stator lamination surface rust-proof treatment method, comprising the following steps: S1: Put the stator lamination in a low-pressure plasma device, and pass in a mixed gas of argon and hydrogen, with a power of 100-200 W, to make the surface have a nano-scale rough structure; S2: After pretreatment, immerse the lamination in a simulated body fluid containing calcium chloride, disodium hydrogen phosphate and polyaspartic acid, and place it at 37-42°C to undergo a biomimetic mineralization reaction:
[0007] Form a hydroxyapatite biomimetic film, and at the same time, polyaspartic acid is adsorbed on the film surface to regulate crystal growth; S3: Prepare an ethanol-water solution containing 2-5 mmol / L calixarene derivative and 1-3 mmol / L β-cyclodextrin, and immerse the lamination for 15-25 minutes. The calixarene and β-cyclodextrin form a nano-scale anti-rust film through host-guest self-assembly. The chemical formula of the calixarene derivative is C 40 H 32 O4R4, R is a long-chain alkyl group; S4: First, apply a water-based inorganic zinc-rich primer containing 30-40 wt% flaky zinc powder and 10-15 wt% flaky aluminum powder; then apply an intermediate transition layer containing 0.3-0.8 wt% carbon nanotube forest and 2-4 wt% polydopamine, with a dry film thickness of 8-12 μm; finally, apply a topcoat containing 0.5-1.2 wt% MXene nanosheet and 3-5 wt% fluorocarbon resin; S5: On the surface of the coating, spray an organic silicone sealant containing 0.02-0.08 wt% azobenzene photochromic molecules and 1-3 wt% nano-titanium dioxide photocatalyst, and irradiate it with 365 nm ultraviolet light for 5-10 minutes. The azobenzene molecules undergo cis-trans isomerization to fill the coating pores, and at the same time, the titanium dioxide photocatalyst forms a super-hydrophilic self-cleaning layer.
[0008] Preferably, after the biomimetic mineralization coating in S2, microwave-assisted treatment is performed, with a microwave power of 300-500 W and a treatment time of 3-5 minutes.
[0009] Preferably, during the supermolecular self-assembly process in S3, an alternating magnetic field with a frequency of 10-20 kHz and an intensity of 0.5-1 T is applied to promote the directional arrangement of the calixarene derivative along the magnetic field direction.
[0010] Preferably, in S4, the carbon nanotube forest is grown in situ by chemical vapor deposition, with ferrocene as the catalyst precursor and acetylene as the carbon source, at a reaction temperature of 600-700°C for 10-20 minutes.
[0011] Preferably, in S4, the MXene nanosheets are modified by amylation. MXene is dispersed in a toluene solution containing 5-10 wt% 3-aminopropyltriethoxysilane and refluxed at 80-90°C for 6-8 hours to graft amino groups onto its surface.
[0012] Preferably, before the S1 plasma pretreatment, the stator laminations are subjected to ultrasonic-electrochemical combined cleaning, with an ultrasonic frequency of 40 kHz, a current density of 0.5-1 A / dm², and a cleaning solution containing 0.2-0.5 wt% phytic acid and 0.1-0.3 wt% benzotriazole.
[0013] Preferably, in S5, the azobenzene photochromic molecule is grafted onto the organosilicon molecular chain via a click chemical reaction, and the reaction is carried out in a THF solution containing CuSO4・5H2O and sodium ascorbate.
[0014] Preferably, a humidity gradient control process is used during the drying of the S4 coating. First, the coating is dried at a relative humidity of 80-90% for 1-2 hours, and then the relative humidity is reduced to 40-50% for 3-4 hours to promote uniform curing of the coating.
[0015] Preferably, the S2 simulated body fluid also contains 0.01-0.03 g / L of nanocellulose whiskers, with a length of 100-500 nm and a diameter of 10-30 nm, which are uniformly dispersed in the mineralized film to enhance the toughness of the film layer.
[0016] Preferably, after the S5 photoresponse sealing treatment, the stator lamination is subjected to hot pressing treatment at a temperature of 80-100℃, a pressure of 1-3MPa, and a holding time of 5-10 minutes.
[0017] (iii) Beneficial technical effects Compared with existing technologies, the beneficial effects of this invention are: 1. Combining plasma pretreatment with biomimetic mineralization coating, a nanoscale rough structure and a hydroxyapatite biomimetic film are constructed on the surface of the wafer. This biomimetic film not only exhibits excellent corrosion resistance but also achieves self-repair of localized damage through a simulated biomineralization process, effectively resisting corrosive media such as chloride ions. Supramolecular self-assembly technology utilizes the host-guest interaction between calixarene and β-cyclodextrin to form a dense nanoscale protective film. This film exhibits dynamic response characteristics, adapting to environmental changes and enhancing its protective capabilities.
[0018] 2. A water-based inorganic zinc-rich primer provides electrochemical protection; flake zinc powder and aluminum powder form a conductive network, sacrificing the anode to protect the substrate. A carbon nanotube forest and a polydopamine interlayer enhance interlayer bonding and block corrosive media penetration through the shielding effect of carbon nanotubes. MXene nanosheets and a fluorocarbon resin topcoat impart excellent chemical stability and hydrophobic properties to the coating. Photoresponsive pore-sealing utilizes the photochromic properties of azobenzene molecules to fill coating pores, combined with the photocatalytic self-cleaning function of titanium dioxide, further enhancing the durability of the protective layer.
[0019] 3. This process utilizes water-based coatings and green chemical reagents, reducing the use of organic solvents and heavy metals, thus meeting environmental protection requirements. Microwave-assisted treatment and alternating magnetic field modulation technologies enable precise process control, improving production efficiency and quality stability. Testing shows that the treated stator laminations exhibited over 2000 hours of rust prevention in salt spray tests, more than three times that of traditional processes. Their service life was extended by 2.5 times under high temperature and humidity environments, effectively solving the corrosion problem of motor stator laminations and driving the upgrading of high-end motor manufacturing technology. Attached Figure Description
[0020] Fig. 1 This is a flowchart of a method for rust prevention treatment of stator lamination surface disclosed in this invention; Fig. 2 This is a line graph comparing the duration of salt spray and damp heat tests for the examples and comparative examples; Fig. 3 This is a comparison chart of the coating performance of the examples and the comparative examples; Fig. 4 This is a radar comparison chart created by standardizing the performance data of the examples and comparative examples. Detailed Implementation
[0021] according to Figs. 1 to 4 The specific embodiments of the present invention are as follows: Example 1: Rust prevention treatment of stator laminations under normal operating conditions S1: Plasma pretreatment A silicon steel stator lamination measuring 100mm × 100mm × 0.5mm was placed in a low-pressure plasma apparatus (model: PD-500) and a mixture of argon (99.99% purity) and hydrogen (99.9% purity) at a volume ratio of 3:1 was introduced. The apparatus was set to a pressure of 80Pa, a power of 150W, and a processing time of 8 minutes. After processing, scanning electron microscopy (SEM) revealed a uniformly distributed nanoscale uneven structure on the lamination surface, with the roughness Ra increasing from 0.8μm before processing to 1.8μm.
[0022] S2: Biomimetic mineral coating Preparation of simulated body fluid: Weigh 1.2g calcium chloride, 0.8g disodium hydrogen phosphate, and 0.08g polyaspartic acid, and dissolve them in 1L deionized water. Completely immerse the pretreated wafer in the solution and place it in a constant temperature water bath (temperature controlled at 39℃) for 2.5 hours. After removal, rinse three times with deionized water and air dry naturally. X-ray diffraction analysis confirmed the formation of a hydroxyapatite biomimetic film on the wafer surface, with a film thickness of approximately 800nm.
[0023] S3: Supramolecular self-assembly Preparation of the self-assembled solution: Dissolve 3 mmol / L calixarene derivative and 2 mmol / L β-cyclodextrin in an ethanol-water mixture, and adjust the pH to 5.5 with hydrochloric acid. Immerse the wafer in the solution for 20 minutes while applying an alternating magnetic field with a frequency of 15 kHz and an intensity of 0.8 T. After removal, rinse with ethanol and dry in a vacuum drying oven at 60 °C for 1 hour.
[0024] S4: Preparation of Gradient Composite Coating Primer coating: Prepare a water-based inorganic zinc-rich primer containing 35wt% flake zinc powder (particle size 1-5μm) and 12wt% flake aluminum powder (particle size 2-6μm). Apply by spraying, control the dry film thickness to 15μm, and dry at 80℃ for 30 minutes.
[0025] Transition layer coating: Carbon nanotube forests were grown in situ on the primer surface via chemical vapor deposition. Ferrocene (0.5 g) was used as the catalyst precursor, and acetylene (flow rate 50 sccm) was used as the carbon source. The reaction was carried out at 650 °C for 15 minutes to form a carbon nanotube layer with a diameter of 20 nm and a height of 8 μm. Subsequently, an intermediate layer containing 3 wt% polydopamine was coated, resulting in a dry film thickness of 10 μm, which was then dried at room temperature for 2 hours.
[0026] Topcoat coating: 0.8wt% amino-modified MXene nanosheets (1-3μm in diameter) and 4wt% fluorocarbon resin are dispersed in deionized water and sprayed to form a topcoat layer with a dry film thickness of 12μm. The coating is cured at 120℃ for 1 hour.
[0027] S5: Photoresponsive sealing treatment A silicone sealing agent was prepared, containing 0.05 wt% azobenzene photochromic molecules and 2 wt% nano-titanium dioxide (particle size 20 nm). A 2 μm thick sealing layer was formed on the coating surface using a spraying method, followed by irradiation with a 365 nm UV lamp (50 W power, 10 cm distance) for 8 minutes.
[0028] Example 2: Rust prevention treatment specifically for high humidity environments S1: Plasma pretreatment A silicon steel stator lamination measuring 100mm × 100mm × 0.5mm was placed in a low-pressure plasma apparatus (model: PD-500), and a mixture of argon (99.99% purity) and hydrogen (99.9% purity) was introduced, maintaining a volume ratio of 3:1. The apparatus pressure was set to 90Pa, power to 180W, and processing time to 9 minutes. After processing, the microstructure of the lamination surface was observed using a scanning electron microscope (SEM). The results showed that a denser and deeper nanoscale uneven structure was formed on the lamination surface, and the roughness Ra significantly increased from 0.8μm before processing to 2.1μm. This change in surface morphology is beneficial for the adhesion of subsequent coatings. S2: Biomimetic mineral coating A special simulated body fluid was prepared: 1.2g calcium chloride, 0.8g disodium hydrogen phosphate, and 0.08g polyaspartic acid were weighed, and 0.02g / L nanocellulose whiskers (300nm in length and 20nm in diameter) were added. All raw materials were completely dissolved in 1L deionized water. The pre-treated wafer was completely immersed in this simulated body fluid and then placed in a constant temperature water bath at 41℃ for 3 hours. After the reaction, the wafer was removed and rinsed three times with deionized water to remove any residual solution from the surface, and then air-dried under natural conditions. X-ray diffraction (XRD) analysis confirmed the formation of hydroxyapatite (Ca) on the surface of the wafer. 10 (PO4)6(OH)2) biomimetic membrane, due to the addition of nanocellulose whiskers, the membrane structure is more compact and the membrane thickness reaches 1000nm. S3: Supramolecular self-assembly Preparation of enhanced self-assembly solution: 4 mmol / L calixarene derivative (chemical formula C) 40 H 32 O4(C 12 H 25 4) 3 mmol / L β-cyclodextrin was dissolved in an ethanol-water mixture (volume ratio 1:4), and the pH of the solution was adjusted to 5.5 with hydrochloric acid. The wafer was immersed in this solution while an alternating magnetic field (generated by an electromagnetic coil) with a frequency of 15 kHz and an intensity of 1.0 T was applied for 22 minutes. After removal, excess solution was rinsed off the wafer surface with ethanol, and then it was dried in a vacuum drying oven at 60℃ for 1 hour. Testing showed that this treatment significantly improved the stability and uniformity of the film layer under high humidity conditions. S4: Preparation of Gradient Composite Coating Primer coating A high-protection water-based inorganic zinc-rich primer was formulated, containing 38 wt% flake zinc powder (particle size 1-5 μm) and 13 wt% flake aluminum powder (particle size 2-6 μm). The primer was evenly applied to the surface of the die-cutting using a spraying method. By precisely controlling the spraying parameters, a dry film thickness of 16 μm was achieved. The die-cutting was then placed in an 80°C drying oven for 30 minutes to allow the primer to fully cure. Transition layer coating In-situ growth of carbon nanotube forests on a primer surface was achieved via chemical vapor deposition. Ferrocene (0.5 g) was used as the catalyst precursor, and acetylene (50 sccm flow rate) was used as the carbon source. The reaction temperature was set at 650 °C, and the reaction time was 15 minutes, ultimately forming a carbon nanotube layer with a diameter of 20 nm and a height of 10 μm. Subsequently, an intermediate layer containing 3 wt% polydopamine was coated onto the surface of the carbon nanotube layer, with the dry film thickness controlled at 10 μm. The layer was then dried at room temperature for 2 hours to allow the intermediate layer to fully adhere and cure. Topcoat coating 1.0 wt% aminated MXene nanosheets (1-3 μm in diameter) and 5 wt% fluorocarbon resin were dispersed in deionized water and thoroughly stirred. The mixture was then sprayed onto the surface of the transition layer to form a topcoat layer, with the dry film thickness controlled at 13 μm. The coated sheet was then placed in a curing oven at 120°C for 1 hour to cure, allowing the topcoat layer to form a dense protective structure. S5: Photoresponsive sealing treatment A high-performance silicone sealing agent was formulated, containing 0.06 wt% azobenzene photochromic molecules and 2 wt% nano-titanium dioxide (particle size 20 nm). A 2 μm thick sealing layer was formed on the coating surface using a spraying method, followed by irradiation with a 365 nm UV lamp (50 W power, 10 cm distance) for 9 minutes. After sealing, the die was placed in a hot press and subjected to hot pressing at 100℃ and 2 MPa for 8 minutes to ensure a tighter bond between the sealing layer and the coating, further enhancing the coating's protective performance in high humidity environments. Example 3: Enhanced rust prevention treatment under high-temperature conditions S1: Plasma pretreatment A silicon steel stator lamination measuring 100mm × 100mm × 0.5mm was placed in a low-pressure plasma device (model: PD-500), and a mixture of argon (99.99% purity) and hydrogen (99.9% purity) gas (volume ratio 3:1) was introduced. The device pressure was set to 70Pa, the power to 120W, and the processing time to 7 minutes. After processing, the surface of the lamination was observed using a scanning electron microscope (SEM). A certain number of nanoscale uneven structures were observed, with a roughness Ra reaching 1.6μm. This roughness ensures good adhesion of subsequent coatings without excessively affecting the lamination's performance. S2: Biomimetic mineral coating First, a simulated body fluid was prepared: 1.2g calcium chloride, 0.8g disodium hydrogen phosphate, and 0.08g polyaspartic acid were weighed and dissolved in 1L deionized water. The pretreated wafer was completely immersed in the simulated body fluid and placed in a constant temperature water bath at 39℃ for 2.5 hours to allow a preliminary hydroxyapatite biomimetic film to form on the wafer surface. Then, the mineralized wafer underwent microwave-assisted treatment at 400W for 4 minutes. This treatment optimized the internal structure of the film, significantly reducing the porosity to 4%, effectively improving the film's protective capability under high-temperature environments. X-ray diffraction (XRD) analysis confirmed that the main component of the film was hydroxyapatite (Ca). 10 (PO4)6(OH)2), with a film thickness of approximately 800 nm. S3: Supramolecular self-assembly Preparation of a special self-assembling solution: 3 mmol / L calixarene derivative (chemical formula C) 40 H 32 O4(C 12 H 25 4) 2 mmol / L β-cyclodextrin was dissolved in an ethanol-water mixture (volume ratio 1:4), the pH was adjusted to 5.5 with hydrochloric acid, and 0.1% graphene quantum dots were added to enhance the thermal conductivity of the film. The wafer was immersed in the solution while an alternating magnetic field (generated by an electromagnetic coil) with a frequency of 12 kHz and an intensity of 0.8 T was applied for 20 minutes. After removal, the wafer surface was rinsed with ethanol to remove any residual solution, and then dried in a vacuum drying oven at 60℃ for 1 hour. Testing showed that the film with added graphene quantum dots exhibited significantly improved thermal stability and thermal conductivity at high temperatures. S4: Preparation of Gradient Composite Coating Primer coating A high-temperature resistant water-based inorganic zinc-rich primer was formulated, comprising 35 wt% flake zinc powder (particle size 1-5 μm), 12 wt% flake aluminum powder (particle size 2-6 μm), and 0.5% high-temperature resistant ceramic powder. The primer was applied by spraying, controlling the dry film thickness to 14 μm, and then dried at 80℃ for 30 minutes to allow full curing, forming a base layer with good high-temperature resistance and rust prevention properties. Transition layer coating In-situ growth of carbon nanotube forests on a primer surface was achieved via chemical vapor deposition. Ferrocene (0.5 g) was used as a catalyst precursor, and acetylene (50 sccm flow rate) as the carbon source. The reaction was carried out at 650 °C for 15 minutes to form a carbon nanotube layer with a diameter of 20 nm and a height of 8 μm. Subsequently, an intermediate layer containing 4 wt% polydopamine was coated, resulting in a dry film thickness of 9 μm. This layer was then dried at room temperature for 2 hours to enhance the adhesion and protective properties of the transition layer. Topcoat coating The topcoat raw materials were formulated, using fluorinated silicone resin as the main film-forming substance, and dispersed in a suitable solvent. A topcoat layer was formed on the surface of the transition layer by spraying, controlling the dry film thickness to 11 μm, and then cured at 120℃ for 1 hour to form a dense and high-temperature resistant protective layer. S5: Photoresponsive sealing treatment A silicone sealing agent was formulated containing 0.05 wt% azobenzene photochromic molecules and 3% nano-titanium dioxide (particle size 20 nm). A 2 μm thick sealing layer was formed on the coating surface using a spray method, followed by irradiation with a 365 nm UV lamp (50 W, 10 cm distance) for 8 minutes. After irradiation, the wafer was placed in an 80℃ dry environment for curing. During curing, the ambient humidity was gradually reduced from 80% to 40%, ensuring the sealing layer fully cured under high-temperature and dry conditions, further improving the sealing and protective performance of the coating under high-temperature operating conditions.
[0029] Comparative example: Traditional anti-rust paint coating process Step 1: Cleaning and degreasing The stator laminations were immersed in an aqueous solution containing 5% sodium hydroxide and ultrasonically cleaned at 60°C for 15 minutes to remove oil stains.
[0030] Step 2: Apply anti-rust paint Spray with traditional oil-based epoxy anti-rust paint, dry film thickness 30μm, and air dry for 24 hours.
[0031] Step 3: Apply topcoat Spray polyurethane topcoat, dry film thickness 20μm, cure at room temperature for 48 hours.
[0032] The table below compares the duration of salt spray and damp heat tests between the examples and comparative examples: Table 1
[0033] The salt spray and damp heat test durations of all three embodiments significantly exceeded those of the comparative example. Example 2 showed the best performance, with a salt spray test duration 4.17 times longer and a damp heat test duration 7.5 times longer than the comparative example, demonstrating that the method of this invention significantly improves the rust and corrosion resistance of stator laminations.
[0034] The performance comparison between the examples and the comparative examples is shown in the table below: Table 2
[0035] The coatings in the example group all achieved the highest adhesion level of 0, with a surface contact angle exceeding 110° and strong hydrophobicity. Although the production cost was higher than that of the comparative example, the performance advantage was significant. The comparative example had an adhesion level of only 2, a low surface contact angle, and poor protective performance.
[0036] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for rust prevention treatment of stator lamination surface, characterized in that, Includes the following steps: S1: Place the stator laminations in a low-pressure plasma device, introduce a mixture of argon and hydrogen gas, and process them with a power of 100-200W to create a nanoscale rough structure on the surface. S2: Immerse the pretreated wafers in a simulated body fluid containing calcium chloride, disodium hydrogen phosphate, and polyaspartic acid, and let them stand at 37-42℃ to allow a biomimetic mineralization reaction to occur. A hydroxyapatite biomimetic membrane is formed, while polyaspartic acid is adsorbed on the membrane surface to regulate crystal growth. S3: Prepare an ethanol-water solution containing 2-5 mmol / L calixarene derivative and 1-3 mmol / L β-cyclodextrin. Immerse the wafer in the solution for 15-25 minutes. The calixarene and β-cyclodextrin self-assemble through host-guest interactions to form a nanoscale anti-rust film. The chemical formula of the calixarene derivative is C1. 40 H 32 O4R4, where R is a long-chain alkyl group; S4: First, apply a water-based inorganic zinc-rich primer containing 30-40 wt% flake zinc powder and 10-15 wt% flake aluminum powder; then apply an intermediate transition layer containing 0.3-0.8 wt% carbon nanotube forest and 2-4 wt% polydopamine, with a dry film thickness of 8-12 μm; finally, apply a topcoat containing 0.5-1.2 wt% MXene nanosheets and 3-5 wt% fluorocarbon resin. S5: Spray an organosilicon sealing agent containing 0.02-0.08wt% azobenzene photochromic molecules and 1-3wt% nano-titanium dioxide photocatalyst onto the coating surface. After irradiation with 365nm ultraviolet light for 5-10 minutes, the azobenzene molecules undergo cis-trans isomerization to fill the pores of the coating, while the titanium dioxide photocatalyzes the formation of a super-hydrophilic self-cleaning layer.
2. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, It also includes microwave-assisted treatment after S2 biomimetic mineralization coating, with microwave power set at 300-500W and treatment time at 3-5 minutes.
3. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, It also includes applying an alternating magnetic field with a frequency of 10-20 kHz and an intensity of 0.5-1 T during the self-assembly of S3 supramolecular molecules to promote the directional alignment of calixarene derivatives along the direction of the magnetic field.
4. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, The carbon nanotube forest in S4 is grown in situ by chemical vapor deposition, using ferrocene as a catalyst precursor and acetylene as a carbon source, and reacts at 600-700℃ for 10-20 minutes.
5. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, In S4, the MXene nanosheets are modified by amination. MXene is dispersed in a toluene solution containing 5-10 wt% 3-aminopropyltriethoxysilane and refluxed at 80-90°C for 6-8 hours to graft amino groups onto its surface.
6. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, Before S1 plasma pretreatment, the stator laminations were subjected to ultrasonic-electrochemical combined cleaning. The ultrasonic frequency was 40 kHz, the current density was 0.5-1 A / dm², and the cleaning solution was an aqueous solution containing 0.2-0.5 wt% phytic acid and 0.1-0.3 wt% benzotriazole.
7. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, In S5, the azobenzene photochromic molecule is grafted onto the organosilicon molecular chain via a click chemical reaction, which is carried out in a THF solution containing CuSO4・5H2O and sodium ascorbate.
8. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, During the drying process of the S4 coating, a humidity gradient control process is adopted. First, the coating is dried at a relative humidity of 80-90% for 1-2 hours, and then the relative humidity is reduced to 40-50% for 3-4 hours to promote uniform curing of the coating.
9. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, The S2 simulated body fluid also contains 0.01-0.03 g / L of nanocellulose whiskers, with a length of 100-500 nm and a diameter of 10-30 nm, which are uniformly dispersed in the mineralized film to enhance the toughness of the film layer.
10. The method for rust prevention treatment of stator lamination surface according to claim 1, characterized in that, After the S5 photoresponse sealing treatment, the stator laminations are hot-pressed at a temperature of 80-100℃, a pressure of 1-3MPa, and a holding time of 5-10 minutes.